Analisis Rasio Profitabilitas Pada Pt Astra Agro Lestari Tbk Periode 2020-2024 - Satel, Suardi; Yuliana; Maksum (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2025)
The profitability ratio is a measure of a company's success based on the efficiency of its capital usage. To calculate a company's profitability, financial reports are needed at a specific time. The profitability ratio is necessary to determine the company's ability to generate profits. This research on PT Astra Agro Lestari Tbk pada periode 2020-2024. In this study, the author used a quantitative descriptive research method. The data and sources of data used in this study are secondary data obtained from the official website of PT Astra Agro Lestari Tbk. The quantitative method used in this study is the calculation of gross profit margin, net profit margin, return on assets (ROA), and return on equity (ROE). The results of the analysis show that the gross profit margin, net profit margin, ROA, and ROE are calculated as follows: The analysis of the company’s financial performance over the past five years (2020–2024) highlights significant fluctuations in gross profit margin, net profit margin, ROA, and ROE. The gross profit margin increased from 1.75% in 2020 to 25.26% in 2021, but then decreased significantly in subsequent years before rising again to 27.38% in 2024. The net profit margin and ROA also exhibited an up-and-down trend. The net profit margin reached its lowest point at 2.26% in 2024, while ROA peaked at 6.02% in 2022 before declining. ROE initially declined, then rose to 6.68% in 2023 before declining again.